Dual advancement of marine economic growth and environmental governance: an empirical analysis of China’s Marine Economic Development Pilot Zones - Zhiyong Song; Zechen Li; Yipin Zhang (Frontiers in Marine Science)
IntroductionThis research aims to empirically investigate the dual effects of establishing the Marine Economic Development Pilot Zone (MEDPZ) on marine economic growth and environmental governance. The study focuses on China’s coastal provinces, where MEDPZs have been implemented, to assess their impacts on both economic and environmental aspects.MethodsThe study employs a Time-varying difference-in-differences (DID) model based on panel data from China’s coastal provinces. This method allows for assessing the causal impact of MEDPZ establishment on marine economic growth and environmental governance by comparing pilot provinces with non-pilot provinces over time.ResultsThe establishment of MEDPZ has significantly enhanced marine economic growth and environmental governance in the pilot provinces. Specifically, marine economic growth increased by 1.222 percentage points, while environmental governance improved by 0.748. Additionally, the impact of MEDPZ establishment varied spatially across different marine economic circles. The northern marine economic circle experienced the most substantial economic growth and environmental governance benefits. The southern marine economic circle saw a significant increase in economic growth but a relatively minor improvement in environmental governance. In contrast, the eastern marine economic circle was not substantially affected.DiscussionThe findings suggest that the establishment of MEDPZ has effectively boosted the competitiveness of the marine economy in pilot provinces while mitigating adverse environmental impacts. This is achieved through promoting scientific and technological advancement and strengthening government regulation. The study provides a scientific basis for policymakers to formulate and implement marine economic development strategies that consider regional differences, enhance financial support for marine science and technology R&D, and enforce stricter regulations for marine environmental protection.